Innovation of Otak-otak based on sweet potatoes - Cantika Choirunnisa; Eva Mardiyana (Publikasi Indonesia, 2024)
This study aims to evaluate the innovation of making otak-otak by replacing tapioca flour with sweet potatoes as the basic ingredient of otak-brain. Otak-otak is a traditional Indonesian food that is generally made from fish, tapioca flour, and other spices. Along with increasing awareness of healthier lifestyle patterns, these innovations are expected to offer more nutritious alternatives. Sweet potatoes with low glycemic content and high fiber are expected to increase the nutritional value of the brain and support digestive health and weight management. The research method used is an experimental method. The manufacturing process involves shredded sweet potatoes, processing ebi, processing other ingredients, and steaming. The product quality assessment was carried out by an organoleptic test involving 50 panelists to assess aspects of taste, color, texture, aroma, and appearance. The results of the organoleptic test showed that the tuber-based brains were well-received by the panelists. Taste rating 86% of panelists rated the product as good to very tasty. The color of the product was considered attractive by 78% of the panelists. The texture of the product was rated soft by 70% of the panelists, and the assessment of aroma and appearance had positive values, 86%, and 76% respectively by the panelists. The results of this study state that brain-brain innovation by using sweet potatoes as a substitute for tapioca flour has succeeded in producing healthier and still delicious products. In addition to being beneficial to health, the use of sweet potatoes can also support the local economy and strengthen food security. Therefore, it is hoped that this research can be useful for people who are interested in tuber-based brains.